The Role of Vitamin D in Pregnant Women in Birth Weight of Neonates - Rajuddin Rajuddin; Derevie Hendryan Moulina; Munawar; Cut Meurah Yeni; Hilwah Nora (Indonesian Society of Obstetrics and Gynecology, 2023)
Objective: To determine the relationship between serum vitamin D levels in third trimester mothers and newborn birthttweight. Method: The study was conducted at the maternity ward of Dr. Zainoel Abidin General Hospital in Banda Aceh, Indonesia. Maternal and infant serum vitamin D levels were measured using the Automatic Chemiluminescence Immunoassay Analyzer (CLIA) method. Blood samples were collected from mothers in the third trimester and from infants after delivery. Spearman's correlation rank test was employed with a confi dence level of 95%. Vitamin D levels were categorized as suffi cient, insuffi cient, and defi cient. Results: A total of 39 pregnant women with an average age of 30.38 ± 6.21 years participated in the study, with a predominance of 38-39 weeks of gestation (35.9%). The mean vitamin D levels in mothers and neonates were 17.4 ng/mL and 17.6 ng/mL, respectively (p = 0.003, R = 0.462). The average birth weight of the babies was 3,100 grams, ranging from 2,100 grams to 4,200 grams (p = 0.185, R = 0.217). Both variables showed a positive correlation with varying strength of the relationship. Conclusion: Maternal serum vitamin D levels in the third trimester exhibited a positive correlation with serum vitamin D levels in neonates with moderate strength, but there was no correlation with birth weight. The evaluation of maternal third-trimester serum vitamin D levels can serve as a predictor of neonatal vitamin D levels. Keywords: birth weight, neonates, pregnancy, vitamin D. Abstrak Tujuan: Untuk menilai pengaruh hubungan kadar vitamin D serum ibu trimester ketiga terhadap kadar vitamin D dan berat badan neonatus yang dilahirkan. Metode: Penelitian ini studi observasional korelatif dengan desain potong lintang yang dilakukan pada kamar bersalin RSUD dr. Zainoel Abidin Banda Aceh. Pengukuran kadar vitamin D serum ibu dan bayi dilakukan dengan metode Automatic Chemiluminescence Immunoassay Analyzer (CLIA). Analisis data dengan melakukan Uji Spearman's correlation rank test untuk menilai kekuatan hubungan dua variabel. Hasil: Sebanyak 39 ibu hamil usia 30,38 ± 6,21 tahun terlibat dalam penelitian ini dengan dominasi usia kehamilan 38-39 minggu (35,9%). Rerata kadar vitamin D ibu dan bayi secara berurutan adalah 17,4 ng/mL dan 17,6 ng/mL (p = 0,003, R = 0,462). Rerata berat badan bayi yang dilahirkan adalah sebesar 3.100 gram dengan rentang 2.100 gram hingga 4.200 gram (p = 0,185, R = 0,217). Kedua variabel didapatkan korelasi positif dengan kekuatan hubungan bervariasi. Kesimpulan: Kadar vitamin D serum ibu trimester ketiga berkorelasi positif terhadap kadar vitamin D serum neonatus yang dilahirkan dengan kekuatan sedang namun tidak berkorelasi terhadap berat badan lahir bayi. Kadar vitamin D serum ibu pada trimester ketiga dapat dijadikan prediktor kadar vitamin D neonatus saat dilahirkan. Kata kunci: berat badan lahir, kehamilan, neonatus, vitamin D.